High prevalence of moderate and severe depressive and anxiety symptoms in polycystic ovary syndrome: a systematic review and meta-analysis - Cooney, Laura G.; Lee, Iris; Sammel, Mary D.; Dokras, Anuja (Human reproduction (Oxford), 2017)
Abstract STUDY QUESTION Do women with polycystic ovary syndrome (PCOS) have an increased prevalence of moderate and severe depressive and anxiety symptoms compared with control women, and do these symptoms correlate with age, BMI, testosterone, hirsutism or insulin resistance (IR)? SUMMARY ANSWER Women with PCOS have significantly increased odds of moderate and severe depressive and anxiety symptoms, independent of obesity, and the symptoms are weakly associated with age, BMI, elevated testosterone, hirsutism and IR. WHAT IS KNOWN ALREADY Previous studies have reported that women with PCOS have an increased prevalence of mild depressive and anxiety symptoms or an increase in mean depression and anxiety scores, although these scores are usually within the normal range. Thus, it is therefore not clear whether these findings are clinically significant. The prevalence of moderate and severe depressive and anxiety symptoms, which require follow-up and would benefit from treatment, is not known in this population. STUDY DESIGN, SIZE, DURATION A comprehensive systematic review (SR) was performed up to January 2016 and included 30 cross-sectional studies, representing 3050 subjects with PCOS and 3858 controls, from 10 different countries. The meta-analysis (MA) on depressive symptoms included 18 studies and the MA on anxiety symptoms included 9 studies. A separate SR identified 15 studies for the meta-regression examining the associations with PCOS-related symptoms or comorbidities. PARTICIPANTS/MATERIALS, SETTING, METHODS All studies included adult women with PCOS, defined by the National Institutes of Health or Rotterdam criteria, and a control group without PCOS. Ovid, Embase, PsychInfo and Cochrane were searched up to January 2016. Included studies used a validated screening tool to compare the prevalence or mean scores of depressive and/or anxiety symptoms. Random effects MA was used to estimate the pooled odds ratio (OR) of depressive and anxiety symptoms. Sensitivity analyses of methodological characteristics and a meta-regression of the pooled standardized mean difference (SMD) to evaluate PCOS-related clinical and laboratory associations were performed. MAIN RESULTS AND THE ROLE OF CHANCE Women with PCOS had increased odds of any depressive symptoms (OR: 3.78; 95% CI: 3.03–4.72; 18 studies) and of moderate/severe depressive symptoms (OR: 4.18; 95% CI: 2.68–6.52; 11 studies). Women with PCOS had increased odds of any anxiety symptoms (OR: 5.62; 95% CI: 3.22–9.80, nine studies) and of moderate/severe anxiety symptoms (OR: 6.55; 95% CI: 2.87, 14.93; five studies). When subjects were matched on BMI, women with PCOS still had higher odds of both depressive (OR: 3.25; 95% CI 1.73–6.09; four studies) and anxiety symptoms (OR: 6.30, 95% CI: 1.88–21.09; three studies). There was no substantial heterogeneity among studies in the overall MA on depressive symptoms (I2 = 22.4%, P = 0.19), but there was significant heterogeneity among studies in the analysis on anxiety symptoms (I2 = 59.6%, P= 0.01). In the meta-regression evaluating pooled SMDs between groups, women with PCOS and concurrent depression had higher mean values of age, BMI, hirsutism score and IR, while women with PCOS and concurrent anxiety had higher mean values of BMI, hirsutism score and free testosterone (P < 0.05 for all comparisons). LIMITATIONS, REASON FOR CAUTION All studies were cross-sectional, thus we can only hypothesize that the diagnosis of PCOS precedes the diagnosis of depression and anxiety. There were large variations in methodological characteristics especially in the studies screening for anxiety; however, they only partly explained effect size variation. WIDER IMPLICATIONS OF THE FINDINGS This evidence-synthesis analysis shows that PCOS diagnosis is associated with an increased risk of moderate and severe depressive and anxiety symptoms and suggests that providers should consider screening women with PCOS for both depression and anxiety. Although age, obesity, hyperandrogenism and IR do not explain the entire association, well-designed studies are needed to assess the impact of treatment of these factors on depressive and anxiety symptoms in women with PCOS. STUDY FUNDING/COMPETING INTEREST(S) No funding was used for this study. There are no conflicts of interest. REGISTRATION NUMBER N/A.